Photodynamic anti-inflammatory activity of meso‑aryl substituted porphyrin derivative on mammalian macrophages - Özgül Hakli; Sümeyye Yarali; Ebru Öner Usta; Furkan Ayaz (Photodiagnosis and Photodynamic Therapy)
Background: Our group focused on a meso‑aryl substituted porphyrin molecule for its photodynamic anti-inflammatory activities on the mammalian macrophages. Materials and methods: The porphyrine derivative previously synthesized in this study was synthesized and characterized by 1H NMR. We then examined their immunomodulatory activities based on the changes in the pro-inflammatory cytokine production levels after LPS stimulation in dark and light activated conditions. Results: Our results suggest that porphyrin derivative had anti-inflammatory photodynamic activity in vitro at subtoxic concentrations. Our study aims to pave a way for anti-inflammatory photodynamic therapy application in the inflammatory and autoimmune disorders. Most of the studies either focus on photodynamic cytotoxicity of the porphyrin derivatives to suppress the inflammation or porphyrin derivatives’ anti-inflammatory activity without the photodynamic activation. Conclusion: Our future studies will focus on the generation and in vitro as well as in vivo characterization of the porphyrin derivatives with anti-inflammatory photodynamic therapy applications. In this way, novel drug candidates that would have lower side effects can be generated for the patients.